Leucaena hedgerow intercropping and cattle manure application in the Ethiopian highlands. I. Decomposition and nutrient release - Lupwayi, N.Z.; Haque, I. (Springer, 1998)
A litter bag technique was used to study the decomposition and release of N, P, K, Ca and Mg from Leucaena leucocephala and L. pallida prunings and cattle manure in a hedgerow intercropping trial conducted in the Ethiopian highlands. Hedgerow inter-cropping (also called alley cropping or alley farming) is an agroforestry system in which trees are grown in dense hedges between alleys where short-cycle crops are grown. The hedges are pruned periodically during the cropping period and the prunings are added to the soil as green manure. Manure was the most resistant to decomposition, losing only 15 percent of its dry matter (DM) in 15 weeks, compared to 41-57 percent lost by leucaena prunings. Large quantities of K (up to 104 kg ha-1) were mineralized from prunings and manure, but Ca and Mg were mostly immobilized. More N and P were released from prunings than from manure, which resulted in net immobilization of these nutrients in the initial stages of decomposition and net mineralization in later stages. Between the leucaenas more N was mineralized and less Ca and Mg were immobilized when L. leucocephala prunings were applied. Fertilizer N increased DM decomposition and N mineralization. Mineralization of the nutrients was constrained by lignin and polyphenol contents. It is concluded that leucaena mulch and cattle manure may be significant sources of N and K for crop growth, but external sources of P, Ca and Mg may be required, particularly in acid soils which have low contents of these nutrients. However, this fertility effect has to be evaluated against the competition effect of trees to predict crop response.